Effects of vitamin C and D on the mRNA expression of angiotensin converting enzyme 2 receptor, cathepsin L, and transmembrane serine protease in the mouse lungs. Issue 1 (31st December 2022) - A. Alruwaili, Meshref; Jarrar, Yazun
ABSTRACT: Vitamins (Vit) C and D are widely used as immunogenic supplements among severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infected patients. The SAR-CoV-2 virus enters into the pulmonary endothelial cells through attachment to angiotensin converting enzyme 2 receptor (Ace2) and the proteolytic activity of Cathepsin L (Ctsl) and transmembrane serine protease 2 (Tmprss2) enzymes. This study aimed to determine the influence of Vit C and D on the mRNA expression of Ace2, Tmprss2, and Ctsl genes in the mouse lungs. Vitamins C and D were administrated to different groups of mice through intra-peritoneal route in doses equivalent to human for 30 days. Then, the mRNA expression of SARS-CoV-2 entry gene was analyzed using qRT-PCR. It is found that Vit D, but not C, upregulated significantly ( P < 0.05) the mRNA expression of Ace2 by more than six folds, while downregulated the expression of Ctsl and Tmprss2 genes by 2.8 and 2.2 folds, respectively. It can be concluded from this study that Vit D alters the mRNA expression of Ace2, Tmprss, and Ctsl genes in the mouse lungs. This finding can help us in understanding, at least in part, the molecular influence of Vit D on genes involved in the entry of SARS-CoV-2 into the cells.